ChemInform Abstract: Preparation and Characterization of SrTiO3—ZnTe Nanocomposites for the Visible‐Light Photoconversion of Carbon Dioxide to Methane. Issue 4 (January 2015) - Ehsan, Muhammad Fahad; Ashiq, Muhammad Naeem; Bi, Feng; Bi, Yiqing; Palanisamy, Sivakumar; He, Tao
Abstract The title nanocomposites containing 25, 50, or 75% ZnTe are hydrothermally synthesized from appropriate mixtures of SrTiO3 and ZnTe in H2O (autoclave, 100 °C, 10 h).